Model Theory Development: Adaptation of Roy, Comfort Kolcaba, & The Andrews/Boyle Transcultural Interprofessional Practice in Breast Cancer Patients - Yaya Fujianti, Mery Eka; Krismiadi, Dedi (Nursing Genius Journal, 2024)
Background Cancer treatment, including chemotherapy, often induces anxiety due to the uncertain prognosis and side effects. Integrating theories such as Roy's adaptation model, Comfort Kolcaba's theory, and The Andrews/Boyle Method The type of research used is research and development with a nursing care approach consisting of assessment, diagnosis, intervention, implementation and evaluation. The research subjects were outpatient breast cancer patients undergoing chemotherapy.  The sample in this study consisted of one patient selected by accidental sampling and the data collection methods used were observation, questionnaires, interviews and patient medical records. Results The primary diagnosis—anxiety—was made based on the integration of the three theoretical models and research results, and the intervention—music therapy and manipulative therapy—was applied using theory and evidence-based practice. Health education about nutrition and diet is the intervention used to identify diarrhea. Patients with chronic wounds who have been diagnosed with skin and tissue integrity disorders are offered culturally-based education and nutrition, and those who struggle with inadequate health management are taught the value of family support. Conclusion The integration of Roy's adaptation model theory, Kolcaba Comfort, and The Andrews/Boyle Transcultural Interprofessional Practice (TIP) model is effective in helping patients to adapt culturally to the symptoms that arise due to chemotherapy so that cancer patients feel comfortable.